碎煤加压气化炉驱动装置的国产化 - 那凤玲; 白柑秋 (Jixie chuandong)
The role of the coal gasifier in the coal chemical industry,the driving device and the important parts localization is introduced.These localization equipment for the coal chemical industry such as coal-to-gas,coal-to-liquid,ammonia and other large projects can be provided to instead of import product.